Developing a rubric matrix for evaluating knowledge management capabilities - Abdul Rahman, Azizah; Hassani, Sara (2010)
For initiating one organization's knowledge management (KM) project, it is essential to evaluate knowledge management capabilities (KMC) of that organization. One of the most popular methods in the phase of evaluating KMC is Fuzzy method that seven attributes of KMC are evaluated by this method. In this paper a rubric matrix is presented to make easy evaluating the value level of each attributes.This rubric is applicable even for whom which are not familiar completely with KM and also is maintained by analyzing and surveying many different researches are done on these attributes.